ANALISIS IMUNOGENISITAS PROTEIN GRA1 DARI HASIL KLONING GEN GRA1 TAKIZOIT Toxoplasma gondii - Didik T Subekti; WT Artama; SH Poerwanto; E Sulistyaningsih; Yulia Sari (BERITA BIOLOGI, 2012)
The study was aimed to analyze the immunogenicity of GRA1 protein derived from clone bearing GRA1 genes from local isolate of Toxoplasma gondii. Analysis of GRA1 protein translated from cDNA of GRA1 is very essential in prior to expressed the gene. Analysis of GRA1 protein derived from clone bearing GRA1 genes was performed using several bioinformatics software which are available as standalone or online software such as CLC Bio Workbench series, BioEdit, BESTORF, GENSCAN, FGENES, BepiPred 1.0, CTL Epitope Finder and SignalP. Translation coding sequences of GRA1 gene into GRA1 peptide sequences revealed 190 amino acids with molecular mass of GRA1 approximately 20.159 kD and isoelectric point at 4.43. GRA1 protein also identified several antigenic domains with six domains were known as epitopes for CD8+/cytotoxic lymphocyte and seven domain as epitopes for B lymphocyte. However, GRA1 protein was considered as good antigen but less immunogenic.